Various ratios of C1-C5 hydrocarbons, gas composition and computed temperature at DSDP Leg 64 Holes - Bernd R T Simoneit (PANGAEA, 1982)
I have evaluated shipboard data and preliminary interpretations related to organic geochemistry in light of additional shore-based analyses. Data on interstitial gas, the C/N ratio, and fluorescence indicate that organic matter was altered by sills and that these were all single intrusions except the upper sill complex at Site 481, which was a multiple emplacement. Site 477 had the highest in situ temperature, estimated from interstitial gas composition to be 225°C.
Supplement to: Simoneit, BRT (1982): Shipboard organic geochemistry and safety monitoring, Leg 64, Gulf of California. In: Curray, JR; Moore, DG; et al. (eds.), Initial Reports of the Deep Sea Drilling Project (U.S. Govt. Printing Office), 64, 723-727, https://doi.org/10.2973/dsdp.proc.64.119.1982